Fluorometer optical path interference via zooplankton phototaxis: Implications for high‐frequency data collection. (9th January 2021) - Moriarty, Vincent W.; Lucius, Mark A.; Johnston, Kenneth E.; Borrelli, Jonathan J.; Mattes, Brian M.; Pezzuoli, Alexander R.; Watson, Campbell D.; Eichler, Lawrence W.; Relyea, Rick A.
Abstract: To measure chlorophyll a (Chl a ) fluorescence ( F chl ), fluorometers use an excitation wavelength that is within the visible spectrum of most zooplankton, and as a result has the potential to cause a phototactic response in zooplankton. The transparent bodies of herbivorous zooplankton may allow viable chlorophyll a within an individual's digestive tract to fluoresce in response to sensor excitation light, resulting in measurement bias. To test for this bias, a fully factorial (± zooplankton and ± light) experiment was conducted in an oligotrophic lake. Excitation light from fluorometers triggered a positive phototactic response during nighttime hours, resulting in swarms of zooplankton congregating beneath the sensor. The maximum hourly mean F chl from nighttime/open treatments was higher and more variable than nighttime/zooplankton exclusion treatments, with the greatest single hour difference of 7.34 relative fluorescence units (RFU) vs. 0.26 RFU. In open treatments, sustained periods of F chl exceeded 31x the values of exclusion treatments. A second series of experiments pulsed excitation lights in alternating periods in order to characterize zooplankton response times. Sensor bias was detected in as little as 20 s after initial illumination. Collectively, these results suggest that swarms of phototactic zooplankton can cause substantial bias in F chl measurements at night. To correct for this bias, post‐processing methods using time series decomposition were demonstrated to remove the majority of F chl bias.